Actions to reduce the impact of construction products on indoor air: outcomes of the European project Healthy Air - Bluyssen, Philomena M.; de Richemont, Sabine; Crump, Derrick; Maupetit, Francois; Witterseh, Thomas; Gajdos, Petr (Sage, 2010)
The European project - HealthyAir is a network project involving six institutions in Europe on actions and activities that address the effects of construction products on indoor air. Different ways to improve indoor air quality were reviewed, ranging from source control to education of occupants on how to manage the built environment to achieve healthy and acceptable indoor air. Through literature study, organised workshops with scientific experts and building professionals as well as via interviews with three stakeholder groups: producers of construction products, architects and housing corporations; requirements for information, guidance and actions to improve indoor air quality were identified. These requirements formed the basis of a possible approach to improve indoor air quality: education and awareness, regulations and policies and further research and development.
Keywords: European project Indoor air quality Construction products End-users' requirements Built environment Regulations and policies buildings quality